Anaemia in patients with chronic liver disease and its association with morbidity and mortality following liver transplantation. (May 2018) - Collas, Oliver; Robertson, Francis P.; Fuller, Barry J.; Davidson, Brian R.
Abstract: Pre-operative anaemia and the need for intra-operative transfusion have been associated with increased morbidity and mortality following cardiac and major non-cardiac surgery. Anaemia is highly prevalent in patients with severe chronic liver disease. Whether this correlates with an altered morbidity and mortality following liver transplant has not been established. Methods: Prospectively collected data was analysed for the period 1998–2012. Donor and recipient characteristics, blood profiles and complications were recorded. Graft and patient survival was calculated. All patients were followed up for 1 year or until death. Pre-operative haemoglobin levels were correlated with patient demographics and outcome using a binary logistic regression analysis. Results: Pre-operative anaemia, according to WHO criteria, occurred in 73% of patients. Anaemia was more common with advanced liver disease (higher MELD score). As MELD score increased, Haemoglobin levels dropped. Anaemic patients were more commonly transfused (p < 0.001), spent longer ventilated (7 day vs 5 days, p = 0.005) and required longer ITU stays (8 days vs 6 days, p = 0.015). Pre-operative anaemia did not correlate with patient morbidity or mortality. Conclusions: Reduced haemoglobin levels reflect the severity of chronic liver disease but are not an independent risk factor for a poor outcome following liver transplantation. Highlights: Anaemia is highly prevalent in patients undergoing liver transplant (73%). Unlike in other major surgery, anaemia is not associated with an increased risk of mortality post liver transplant. Haemoglobin levels are inversely correlated with MELD scores. Anaemia likely reflects increased pre-operative disease burden and poorer pre-operative physiology.